The Implementation of Law Enforcement Against Criminal Acts of Mobbing Against Persons is Reviewed by Article 170 Paragraph (2) of the Criminal Code - Prihartono Prihartono; Muhammad Yusuf Siregar; Wahyu Simon Tampubolon; Risdalina Risdalina (International Journal Labs, 2022)
Background: Indonesia is a country of law, the statement contained in the Explanation of the 1945 Constitution states that